2022
DOI: 10.3390/ijerph191811446
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Perceptions of Korean Older Adult Patients and Caregivers about Polypharmacy and Deprescribing

Abstract: Polypharmacy is continuously increasing among older adults. The resultant potentially inappropriate medications (PIMs) can be harmful to patient health. Deprescribing refers to stopping or reducing PIMs. In this study, the current status of polypharmacy and willingness of older adults to deprescribe were investigated among patients and caregivers who are not associated with one another. The survey used the Korean translated version of the revised Patients’ Attitude Towards Deprescribing (rPATD) Scale. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…This was different from the most common cause of deprescribing in other specialties such as ADRs ( Goyal et al, 2020 ). Also, most patients and caregivers (77.6% and 76.4%, respectively) in Korea wanted to reduce the number of medications ( Lee et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was different from the most common cause of deprescribing in other specialties such as ADRs ( Goyal et al, 2020 ). Also, most patients and caregivers (77.6% and 76.4%, respectively) in Korea wanted to reduce the number of medications ( Lee et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of deprescribing is also acknowledged not only by healthcare professionals but also by patients and caregivers. One study revealed that over 70% of patients wished to reduce the number of prescriptions, if feasible [19]. Consequently, guidelines such as OncPal [20] and STOPPFrail [21] have been developed to facilitate improved outcomes for advanced cancer patients.…”
Section: Introductionmentioning
confidence: 99%